Effect of Dietary Supplementation of Garlic (Allium sativum) and Black Pepper (Piper nigrum L.) Powder on Growth Performance of Broilers in Konkan Region of India - Bharambe, V. Y.; Shinde, S. S.; Garde, Y. D. (Indian Journal of Hill Farming, 2018)
An experiment was conducted to assess the effect of dietary supplementation of garlic(Allium sativum) bulb and black pepper (Piper nigrum L.) powder as herbal feed additiveson feed intake, growth performance in broilers; A total of 320 day old broilers chicks ofVencobb-400 strain were divided into four treatment groups with four replicates of 20chicks in each treatment using completely randomized design. The control group (C) wasfed on basal diet without any supplementation and other three treatment groups weresupplementation with 0.5% garlic bulb powder 0.5% black pepper powder and 0.5% ofeach supplement (garlic bulb powder and black pepper powder) in G, B and GB groups,respectively statistical analysis of data revealed no effect of garlic and black pepper aloneor no in combination of feed intake of experimental birds. Growth performance andefficiency of feed utilization for growth was significantly (P